If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6g + -2k + 4g + 3k = 0 Reorder the terms: 6g + 4g + -2k + 3k = 0 Combine like terms: 6g + 4g = 10g 10g + -2k + 3k = 0 Combine like terms: -2k + 3k = 1k 10g + 1k = 0 Solving 10g + 1k = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1k' to each side of the equation. 10g + 1k + -1k = 0 + -1k Combine like terms: 1k + -1k = 0 10g + 0 = 0 + -1k 10g = 0 + -1k Remove the zero: 10g = -1k Divide each side by '10'. g = -0.1k Simplifying g = -0.1k
| -(3p-5)=-(p+1) | | 11/2(16+3)=24n | | 9+2x=83 | | 6x+5x-45=75-4x | | (N*N)+5n-6=60 | | 3z-1=8-3z | | 8/1(11) | | 11(x-5)=10(x-5) | | -(x-5)=5x-3(2x+3) | | 11x^2-24x+4=0 | | 3/4x+4=19 | | X+32=-8.5 | | 1+2g=5 | | 20+8=-20 | | 3-0.27= | | 4x+1=x-3 | | -19=5(1+3x)-4(6-5x) | | -2(6-2n)=5(n-1) | | 4(W+1)-7=3(7-1)+W | | 5x+8x-40=80-7x | | 4(6+7)=4*6+x*7 | | s=-16t^2+128t+144 | | 18xy-3x-19xy= | | 24x^2+91x+72=0 | | 5G/7=18 | | -14.1+18.3= | | 4x+9=12+3x | | -7/2-2x=-1/2 | | ((4x^2)-2x+6)/(2x-3) | | 65-7x=2x+23 | | -5(k+3)+4k=3(k-5) | | 80=5*2b |